1998
DOI: 10.2337/diacare.21.11.1848
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in glomerular filtration rate in Japanese patients with type 2 diabetes is linked to atherosclerosis.

Abstract: The decline in GFR in type 2 diabetic patients in the early stages of nephropathy may be due in part to atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 0 publications
7
42
1
4
Order By: Relevance
“…High IMT and stiffness parameter exhibited predictive multivariate odds ratios for concurrent CAD, which were further strengthened by the combination of high IMT and stiffness parameter ; therefore, in addition to the specific characteristics of stiffness parameter , as recently reviewed 4) and reported by us [20][21][22][24][25][26] , our findings suggest that the combination of arterial stiffness and IMT determined by ultrasound is a unique tool for the evaluation of atherosclerosis in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…High IMT and stiffness parameter exhibited predictive multivariate odds ratios for concurrent CAD, which were further strengthened by the combination of high IMT and stiffness parameter ; therefore, in addition to the specific characteristics of stiffness parameter , as recently reviewed 4) and reported by us [20][21][22][24][25][26] , our findings suggest that the combination of arterial stiffness and IMT determined by ultrasound is a unique tool for the evaluation of atherosclerosis in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 84%
“…Increased stiffness parameter of the carotid artery and/or aorta has been reported to be associated with CAD 15,[17][18][19] . We have also demonstrated that stiffness parameter is increased in diabetic patients with chronic kidney disease 20) , latent symptoms of peripheral artery disease 21) , insulin resistance 22,23) , and hypoadiponectinemia 24) . Furthermore, stiffness parameter in T2DM has been found to be, at least in part, reversibly improved by aerobic exercise 25) and the insulin sensitizer pioglitazone 26) .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has previously been shown that patients with type 2 diabetes and a reduced eGFR (calculated by MDRD6 formula) have a similar degree of intrarenal vascular damage irrespective of their AER status [23]. Likewise, a decline in renal function has been reported to be associated with an increase in carotid intimalmedial thickness and an increase in intrarenal arterial resistance index [24]. Thus, not only AER, but also GFR may be a marker of generalised vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…We (24) previously found in patients who had type 2 diabetes with and without microalbuminuria that the stiffness of the carotid artery was associated with GFR but not with albuminuria, independent of other clinical factors. For comparing the magnitude of influence of CKD on stiffness of the four different arterial segments in patients with diabetes, regional PWV values were expressed as percentages relative to the corresponding healthy control mean level and plotted against CKD stages.…”
Section: Discussionmentioning
confidence: 99%